Periampullary Dieulafoy’s Lesion: An Unusual Cause of Gastrointestinal Bleeding - Rana, Surinder S; Bhasin, Deepak K; Gupta, Rajesh; Yadav, Thakur Deen; Gupta, Vivek; Singh, Kartar (JOP. Journal of the Pancreas, 2010)
Context Dieulafoy’s lesion is an unusual cause of gastrointestinal bleeding with the most common location being the stomach. A periampullary location is rare for a bleeding Dieulafoy’s lesion. Case report We present the case of a 52-year-old female who presented with intermittent painless melena. Her upper gastrointestinal endoscopy and colonoscopy were normal. She was a diagnostic challenge as no definite lesion could be identified on capsule endoscopy. However, as there was presence of fresh blood in the proximal jejunum, a push enteroscopy was performed which revealed the presence of fresh blood in the duodenum and proximal jejunum. But no bleeding lesion could be identified. A side view endoscopy was performed which revealed a bleeding periampullary Dieulafoy’s lesion. Immediate hemostasis was achieved with an injection of adrenalin. Other episodes of bleeding occurred and the patient was finally treated surgically. Conclusion A periampullary Dieulafoy’s lesion presenting with obscure gastrointestinal bleed is a diagnostic challenge and can be missed on capsule endoscopy. Image: The application of a hemoclip on the Dieulafoy’s lesion.